2015
DOI: 10.3750/aip2015.45.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Risks to stocks of native trout of the genus Salmo (Actinopterygii: Salmoniformes: Salmonidae) of Serbia and management for their recovery

Abstract: Simonović P., Vidović Z., Tošić A., Škraba D., Čanak-Atlagić J., Nikolić V. 2015. Risks to stocks of native trout of the genus Salmo (Actinopterygii: Salmoniformes: Salmonidae) of Serbia and management for their recovery. Acta Ichthyol. Piscat. 45 (2): 161-173.Background. Insuffi ciently controlled stocking compromises the high diversity of wild trout stocks of Serbia. Native brown trout, Salmo cf. trutta Linnaeus, 1758, and Macedonian trout, Salmo macedonicus (Karaman, 1924), reveal remarkable diversity asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…In the Adriatic region, only MA, AD, and ME phylogenetic lineages are considered autochthonous (Giuffra et al 1994, Apostolidis et al 1997, Snoj et al 2000. The use of mitochondrial DNA (mtDNA) markers (Berg and Ferris 1984, Gyllensten and Wilson 1987, Bernatchez 2001, Suárez et al 2001, Snoj et al 2002, Sušnik et al 2004, Cortey et al 2004, Bardakci et al 2006, Turan et al 2011, Simonović et al 2015 and nuclear markers (Ferguson and Fleming 1983, Antunes et al 2002, Hashemzadeh Sagherloo et al 2012, Pustovrh et al 2014, Araguas et al 2017 revealed that the genus Salmo is genetically a highly structured taxon and therefore, effective conservation strategies need to be focused on the population level. Genetic screening of variation in brown trout, Salmo trutta Linnaeus, 1758, has been largely applied towards evaluating introgression of hatchery strains into wild populations (Hansen and Loeschcke 1994, Arias et al 1995, Largiadèr and Scholl 1995.…”
Section: Introductionmentioning
confidence: 99%
“…In the Adriatic region, only MA, AD, and ME phylogenetic lineages are considered autochthonous (Giuffra et al 1994, Apostolidis et al 1997, Snoj et al 2000. The use of mitochondrial DNA (mtDNA) markers (Berg and Ferris 1984, Gyllensten and Wilson 1987, Bernatchez 2001, Suárez et al 2001, Snoj et al 2002, Sušnik et al 2004, Cortey et al 2004, Bardakci et al 2006, Turan et al 2011, Simonović et al 2015 and nuclear markers (Ferguson and Fleming 1983, Antunes et al 2002, Hashemzadeh Sagherloo et al 2012, Pustovrh et al 2014, Araguas et al 2017 revealed that the genus Salmo is genetically a highly structured taxon and therefore, effective conservation strategies need to be focused on the population level. Genetic screening of variation in brown trout, Salmo trutta Linnaeus, 1758, has been largely applied towards evaluating introgression of hatchery strains into wild populations (Hansen and Loeschcke 1994, Arias et al 1995, Largiadèr and Scholl 1995.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the fact that Romanian rivers are exclusively inhabited by brown trout of the Danubian lineage (Popa et al, 2013). Brown trout of the At lineage have so far been found scattered in Serbia, e.g., in the Gradac River, in the main bed of the Danube River near Veliko Gradište (1059th river kilometer), in the Brankovačka River (Marić et al, 2006), and in the Jerma River (Simonović et al, 2015). Brown trout in streams of the narrower Iron Gate area have never been investigated for their mtDNA haplotypes thus far, only those from the Rečka and Vratna Rivers in the broader Iron Gate area (Marić et al, 2006).…”
mentioning
confidence: 61%
“…There is no evidence of their natural occurrence south and southeast of the Alps; regardless, they predominate as native in the headwaters of the upper Danube in Bavaria and in numerous drainages of the Austrian Danube. One possible explanation for the presence of At haplotypes could be uncontrolled stocking with allochthonous, hatchery-reared brown trout of the Atlantic clade, which were introduced in this way into many streams and rivers throughout the Balkans (Marić et al, 2006;Jadan et al, 2010;Simonović et al, 2015) and Europe (Largiadèr and Scholl, 1996;Osinov and Bernatchez, 1996;Hansen et al, 2000;Weiss et al, 2000Weiss et al, , 2001. Two specimens of the same H3 haplotype were recorded in 2010 in the Danube riverbed by Marić et al (2012) near the city of Veliko Gradište at river kilometer 1059.…”
Section: Discussionmentioning
confidence: 99%
“…Supportive evidence for this can be found in the Danube River basin, that is introgression of alien At1 haplotype of Atlantic brown trout (Marić, Sušnik, Simonović, & Snoj, 2006), which caused the loss of intraspecific variability, following the introduction of alien strains and a change in genetic composition of native brown trout stock of Danube lineage (Simonović et al, 2014). Considering the impact of introduced foreign-sourced brown trout on native brown trout stocks in Serbia, brown trout of the Atlantic lineage was found to be the most invasive alien brown trout strain in Serbia (Simonović et al, 2015).…”
Section: Western Europementioning
confidence: 99%
“…Stocking with alien species has been banned by legislation in many Balkan countries(in 2000 in Serbia; in 2001 in Croatia), although dispersal via the Danube River as a prominent southern Invasive Corridor (Bij de Vaate, Jazdzewski, Ketelaars,Gollasch, & Van der Velde, 2002) continues. However, unintentional introductions of alien fish species and alien trout strains(Simonović et al, 2015) still occur in certain countries, such as Serbia.…”
mentioning
confidence: 99%